PERAN NILAI HEDONIK MEMEDIASI PENGARUH ATMOSFER GERAI TEHADAP PEMBELIAN IMPULSIF (Studi Pada Konsumen Level 21 Mall Denpasar) - Wijaya, I Putu Rama; Warmika, I Gde Ketut (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p09, 2020)
This study  aims  to  determine the effect of the outlet atmosphere on impulsive purchases through hedonic values as a mediator. The research sample was set as many as 75 respondents using a sampling technique that is purposive sampling. The  analysis  technique used  is  path analysis  with  the classic assumption test and the sobel test This research is expected to be able to make empirical contributions about the influence between outlet atmosphere variables, hedonic values, and impulsive purchases for the development of science and become a consideration for company marketing management. The result   showed that the outlet atmosphere had a positive and significant effect on hedonic values. Outlet atmosphere has a positive and significant effect on impulsive purchases. The hedonic value has a positive and significant effect on impulsive purchases. The hedonic value significantly mediates the effect of the outlet atmosphere on impulsive purchases. Keywords: outlet atmosphere, hedonic value, impulsive buying